2013
DOI: 10.3892/or.2013.2951
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-503 acts as a tumor suppressor in glioblastoma for multiple antitumor effects by targeting IGF-1R

Abstract: microRNA (miRNA) dysregulation is associated with various types of human cancer by regulating cancer cell survival, proliferation and invasion. Aberrant expression of microRNA-503 (miR-503) has been reported in several cancer profiles. However, potential linkage of miR-503 levels and the underlying regulatory mechanisms in human glioblastoma multiforme (GBM) remain unclear. In the present study, we showed for the first time that the expression of miR-503 was significantly reduced in GBM tissues and cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
(39 reference statements)
3
34
0
1
Order By: Relevance
“…MicroRNA-503 suppresses proliferation and cell-cycle progression of endometrioid endometrial cancer by negatively regulating cyclin D1 [19]. miR-503 acts as a tumor suppressor in glioblastoma for multiple antitumor effects by targeting IGF-1R [17]. Recently, miR-503 was reported to be downregulated in HCC and involve HCC progression [20].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…MicroRNA-503 suppresses proliferation and cell-cycle progression of endometrioid endometrial cancer by negatively regulating cyclin D1 [19]. miR-503 acts as a tumor suppressor in glioblastoma for multiple antitumor effects by targeting IGF-1R [17]. Recently, miR-503 was reported to be downregulated in HCC and involve HCC progression [20].…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that miR-503 is downregulated in several tumor types including non-small cell lung cancer [14], oral cancer [15], gastric cancer [16], glioblastoma [17]. In these tumors miR-503 functions as tumor suppressor by repressing oncogene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of PYK2 was associated with activation of the PI3K/AKT pathway and poor survival and metastasis in hepatocellular carcinoma [37]. Additionally, as miR-503 targets and inhibits PI3K/AKT activation [40,41], the suppression of miR-503 in recipient cells may result in the up regulation of PI3K/AKT signaling and the subsequent promotion of metastasis.…”
Section: Microparticles Mediate the Enhancement Of Metastatic Traitsmentioning
confidence: 99%
“…One pathway by which miR-503 acts as a tumor suppressor is via downregulation of phosphatidylinositol 3-kinase (PI3K)/AKT signaling (17). The PI3K/AKT signaling pathway plays an important role in the progression of breast cancer (18, 19).…”
Section: Introductionmentioning
confidence: 99%